Organ and tissue donation and transplantation : a perspective of South African Baptists from Baptist Northern Association and its implication for preaching - Clasen, F.J. (University of Pretoria, 2013)
Dissertation (MA (Research in Practical Theology))--University of Pretoria, 2007.